Pengembangan Modul IPA Materi Gaya Terintegrasi Kearifan Lokal Berburu Menggunakan Busur Panah Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV SD Inpres Timika III - Lisna Pasaribu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This reseach was conducted besed on the result of observations where tehe teacher only used a monotonus learning method namely lectures, so that the teaching and learning process was only teacher-centred, the use of learning media was not optimal, and the teaching material and learning used were only extbooks and the teacher had never integrating natural science lesson with local wisdom in papua resulting in low student learning outcomes in natural science subject, style material. This reseach was made with the aim of developing science module that integrates the local papuan wisdom of hunting using bows to improve the learning outcomes of fourth grade student at SD IPRES TIMIKA III. The modules created will be validated by material, media and languange experts to determine the feasibility of the modules that have been developed. The reseach model for this reseach is Borg and Gall reseach and development. The writing of the science module for class IV style material iss divided into 4 successive stages. The first stage is data collection, the second stage is making the initial design, the third module, and the fourth stage is making the final part of the module. After being given the natural sciente teaching module, style material which is integrated wit hpapuan local wisdom, the learning outcomes of student totaled 2505 with an average score of 83,50 with the lowest score being 70 and the highest score being 100 with the percentage of score that achieve the maximum completenes criteria of 100%. Thus the science learning modul, integrated style material, local wisdom, hunting using bows which was developed was effective in improving the learning outcomes of fourth grade students at SD INPRES TIMIKA III.